2018
DOI: 10.15171/jcs.2018.025
|View full text |Cite
|
Sign up to set email alerts
|

Service Quality Gaps in the Provision of Care to Surgical Patients: a Cross-Sectional Study in the Northwest of Iran

Abstract: Introduction: The evaluation of service quality is a key measurement which provides the necessary information for effective decision making and providing high quality care. This study aimed to investigate the factors affecting the service quality gap for the provision of care from the perspective of surgical patients hospitalized in a teaching hospital in the Northwest of Iran in 2015. Methods: In this descriptive cross-sectional study a total of 300 patients and 101 nurses were selected by random sampling me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…24 In the healthcare system, patient satisfaction is the main factor determining the quality of healthcare services and ethical performance. 25,26 Although in the current study excessive expectations of the patients and their companions were reported as barriers in observing the professional ethics standards from nurses' viewpoints, the findings of recent service quality gaps study revealed that the patients’ perceptions of health care services also are lower than their expectations. 26 In the study by McCabe, 27 patients were discontented with empathy, communication, attention, and friendly communication from the nurses.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…24 In the healthcare system, patient satisfaction is the main factor determining the quality of healthcare services and ethical performance. 25,26 Although in the current study excessive expectations of the patients and their companions were reported as barriers in observing the professional ethics standards from nurses' viewpoints, the findings of recent service quality gaps study revealed that the patients’ perceptions of health care services also are lower than their expectations. 26 In the study by McCabe, 27 patients were discontented with empathy, communication, attention, and friendly communication from the nurses.…”
Section: Discussionmentioning
confidence: 51%
“…25,26 Although in the current study excessive expectations of the patients and their companions were reported as barriers in observing the professional ethics standards from nurses' viewpoints, the findings of recent service quality gaps study revealed that the patients’ perceptions of health care services also are lower than their expectations. 26 In the study by McCabe, 27 patients were discontented with empathy, communication, attention, and friendly communication from the nurses. Moreover, the excessive expectations of patients and their relatives are partly due to the lack of receiving suitable information from the nurses during hospitalization.…”
Section: Discussionmentioning
confidence: 51%
“…Even when compared to other sectors, the health sector must manage the quality of its services more strictly, as it directly affects the population's living conditions and wellbeing. The provision of quality health services, therefore, has a positive impact Junior et al BMC Medical Informatics and Decision Making (2022) 22:8 on the economy, which in turn benefits the population as a whole; leading to the conclusion that improving health services is an absolute priority [1].…”
Section: Introductionmentioning
confidence: 99%
“…The present article proposes a hybrid QFD-fuzzy-SERVQUAL approach as a decision support tool for the quality planning of the HUOL surgical centre. In order to develop such approach it was necessary to take the following, it will be necessary to take the following methodological procedure: (1) elaborating and validating the SERVQUAL questionnaire; (2) identifying the main deficiencies of the surgical centre in the perception of the medical team through the application of SERV-QUAL and fuzzy logic; (3) carrying out the construction of the 'house of quality' , through the integration of the QFD-fuzzy-SERVQUAL tools; (4) performing the analysis of the engineering requirements through the 'house of quality' and fuzzy logic; and v) developing an action plan proposal for the surgical centre quality planning, resulting from the QFD-fuzzy-SERVQUAL integration.…”
Section: Introductionmentioning
confidence: 99%
“…Even when compared to other sectors, the health sector must manage the quality of its services more strictly, as it directly affects the population's living conditions and wellbeing. The provision of quality health services, therefore, has a positive impact on the economy, which in turn benefits the population as a whole; leading to the conclusion that improving health services is an absolute priority 1 .…”
Section: Introductionmentioning
confidence: 99%